2019
DOI: 10.3389/fendo.2019.00331
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial-Derived Peptides Are Down Regulated in Diabetes Subjects

Abstract: Background: Mitochondrial dysfunction is implicated in the pathogenesis of Type 2 diabetes (T2D) and the development of diabetes related complications such as cardiovascular disease and stroke. Mitochondria produce several small polypeptides that may influence mitochondrial function and may impact on insulin sensitivity, such as humanin (HN) and the mitochondrial open reading frame of the 12S rRNA type-c (MOTS-c) that are mitochondrial derived proteins (MDP). The aim of this study was to determine M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 56 publications
7
57
0
Order By: Relevance
“…In this study, midlife humanin treatment attenuated the obesity that occurs in mid-life, but did not exacerbate the gradual decline in bodyweight at older ages. This improvement in metabolic parameters has been previously seen in mice treated with HNG and in fact, human studies have found that HN levels were negatively correlated with HbA1c levels and triglyceride levels [29,44]. Taken together, even at the low doses that we administered to middleaged mice, humanin treatment improved several lifespan and healthspan markers such as metabolism, fibrosis, and cognitive decline [41,68].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this study, midlife humanin treatment attenuated the obesity that occurs in mid-life, but did not exacerbate the gradual decline in bodyweight at older ages. This improvement in metabolic parameters has been previously seen in mice treated with HNG and in fact, human studies have found that HN levels were negatively correlated with HbA1c levels and triglyceride levels [29,44]. Taken together, even at the low doses that we administered to middleaged mice, humanin treatment improved several lifespan and healthspan markers such as metabolism, fibrosis, and cognitive decline [41,68].…”
Section: Discussionsupporting
confidence: 75%
“…Circulating levels of humanin correlate with lifespan in different mouse models of aging and bi-weekly injections of the humanin analogue HN-S14G delays the cognitive decline in mice [39][40][41][42]. Another MDP, MOTS-c, has already been associated with longevity in centenarians [43], although association studies of humanin levels in humans have been equivocal [44][45][46]. In this study we further investigated the relationship between humanin, longevity, and healthspan using transgenic worms, multiple mammalian species with divergent lifespans, and also the children of centenarians compared to age-matched controls.…”
mentioning
confidence: 99%
“…While MOTS-c serum levels have recently been reported to negatively correlate with age in a cohort of participants with type 2 diabetes [32], interpretation of this data is confounded by the healthy control group being significantly younger than the diabetic groups. Regardless, our results support this finding and previous observations of lower MOTS-c plasma levels in aged mice, but are in contrast to reported murine skeletal muscle age-associated decline in MOTS-c levels [14].…”
Section: Discussionmentioning
confidence: 95%
“…However, when the ability of the muscle cell to tolerate or adapt to this stress is overwhelmed then MOTS-c levels may decrease along with function of the cell. In support, some studies have reported reduced plasma levels of MOTS-c in people with obesity, type 2 diabetes [32,37] or impaired coronary endothelial function [38], and exogenous MOTS-c treatment restores skeletal muscle insulin sensitivity in mice [14,27].…”
Section: Agingmentioning
confidence: 87%
“…It is possible that the exported MOTS‐c transcript may be cotranslated and translocated to the mitochondria using such mitochondrial‐associated cytoplasmic ribosomes. Work is also in progress to understand cellular cues that induce MOTS‐c expression, and metabolic alterations and inflammation may be key. Similar to HN, MOTS‐c has both intracellular and endocrine roles .…”
Section: Regulatory Peptides Encoded In the Mitochondrial Genome: Newmentioning
confidence: 99%